Genetic disruption of the PI3K regulatory subunits, p85α, p55α, and p50α, normalizes mutant PTPN11-induced hypersensitivity to GM-CSF - Goodwin, Charles B. (Ferrata Storti Foundation, 2012)
Juvenile myelomonocytic leukemia is a lethal disease of children characterized by hypersensitivity of hematopoietic progenitors to granulocyte macrophage-colony stimulating factor. Mutations in PTPN11, the gene encoding the protein tyrosine phosphatase Shp2, are common in juvenile myelomonocytic leukemia and induce hyperactivation of the phosphoinositide-3-kinase pathway. We found that genetic disruption of Pik3r1, the gene encoding the Class IA phosphoinositide-3-kinase regulatory subunits p85α, p55α and p50α, significantly reduced hyperproliferation and hyperphosphorylation of Akt in gain-of-function Shp2 E76K-expressing cells. Elevated protein levels of the phosphoinositide-3-kinase catalytic subunit, p110δ, in the Shp2 E76K-expressing Pik3r1−/− cells suggest that p110δ may be a crucial mediator of mutant Shp2-induced phosphoinositide-3-kinase hyperactivation. Consistently, treatment with the p110δ-specific inhibitor, IC87114, or the clinical grade pan-phosphoinositide-3-kinase inhibitor, GDC-0941, reduced granulocyte macrophage-colony stimulating factor hypersensitivity. Treatment with the farnesyltransferase inhibitor, tipifarnib, showed that Shp2 E76K induces hyperactivation of phosphoinositide-3-kinase by both Ras-dependent and Ras-independent mechanisms. Collectively, these findings implicate Class IA phosphoinositide-3-kinase as a relevant molecular target in juvenile myelomonocytic leukemia.